Flood Hazard Mapping in Residential Area Using Hydrodynamic Model HEC-RAS 5.0 - Muhammad Baitullah Al Amin; Reini Silvia Ilmiaty; Ayu Marlina (Geoplanning: Journal of Geomatics and Planning, 2020)
The flood hazard rating is one of the essential variables in flood risk analysis. The identification of flood-prone areas urgently requires information about flood hazard zones. This research explains the method to develop flood hazard map by using hydrodynamic modeling in the residential areas. The hydrodynamic model used in this research is HEC-RAS 5.0, which can simulate the one- and two-dimensional flow regimes. The study area is Bukit Sejahtera and Tanjung Rawa residences located in Palembang City with a total area of about 200 ha, where the Lambidaro River was frequently overflowing caused flood inundation in the area. There are five indicators of flood hazard being analyzed, i.e., 1) flood depth, 2) flow velocity, 3) energy head, 4) flow force, which is the result of multiplication between flood depth and the square of flow velocity, and 5) intensity, which is the result of multiplication between flood depth and the flow velocity. The simulation results show that the flood hazard rating in the study area ranges from high to low level. The zones with a high flood hazard rating are dominated by the area around or near to the river, whereas the further zones have a moderate and low level of flood hazard rating. The flood depth indicator has a more significant influence than the flow velocity on the flood hazard level in the study area. This research is expected can contribute to the development of flood map and flood control methods in advance.